Assessment of hemispheric dominance for receptive language in pediatric patients under sedation using magnetoencephalography - Rezaie, Roozbeh; Narayana, Shalini; Schiller, Katherine; Birg, Liliya; Wheless, James W.; Boop, Frederick A.; Papanicolaou, Andrew C. (Frontiers in Human Neuroscience, 2014)
Non-invasive assessment of hemispheric dominance for receptive language using Magnetoencephalography (MEG) is now a well-established procedure used across several epilepsy centers in the context of pre-surgical evaluation of children and adults while awake, alert and attentive. However, the utility of MEG for the same purpose, in cases of sedated patients, is contested. Establishment of the efficiency of MEG is especially important in the case of children who, for a number of reasons, must be assessed under sedation. Here we explored the efficacy of MEG language mapping under sedation through retrospective review of 95 consecutive pediatric patients, who underwent our receptive language test as part of routine clinical evaluation. Localization of receptive language cortex and subsequent determination of laterality was successfully completed in 78% (n=36) and 55% (n=27) of non-sedated and sedated patients, respectively. Moreover, the proportion of patients deemed left hemisphere dominant for receptive language did not differ between non-sedated and sedated patients, exceeding 90% in both groups. Considering the challenges associated with assessing brain function in pediatric patients, the success of passive MEG in the context of the cases reviewed in this study support the utility of this method in pre-surgical receptive language mapping.